English Learning: The Use of Artificial Intelligence in Improving Teaching Method Innovation - Andika Andika (BADAN PENERBIT STIEPARI PRESS, 2024)
The purpose of this study is to investigate how well artificial intelligence (AI) works for teaching English. Mixed-methods research is used, integrating qualitative and quantitative techniques. Thirty students of Gajah Sakti Polytechnic, Metro, Lampung who employed AI as a language learning method made up the study participants. The outcomes demonstrated that utilizing AI significantly improved speaking, listening, reading, and writing abilities. These results validate the usefulness of AI in language learning. Furthermore, this work closes the gap left by earlier studies on the application of AI to English language instruction in academic settings. The research's practical implication is that, in order to improve effective and efficient learning outcomes, AI must be included into language learning curriculum. This study adds significantly to our knowledge of how artificial intelligence is used in language acquisition and shows how powerful AI can be in the creation of novel and flexible teaching strategies.